Love in the Spotlight : The Love Script - Book 1 - Shiloh, Toni (Thorndike, Maine : Center Point Large Print, 2023)
"A Hollywood hair stylist: Nevaeh Richards loves making those in the spotlight shine but prefers the anonymity of staying behind her stylist chair, where no one notices her. But when a photo of Nevaeh and Hollywood A-lister Lamont Booker goes viral for all the wrong reasons, her quiet life becomes the number-one trending topic. The silver screens latest heartthrob: Lamont Bookers bold faith has gained him a platform, and the authenticity of his faith is well known . . . until the tabloids cause the world to question everything he claims to be. With his reputation on the line, he finds himself hearing out his agents push for a fake relationship -- something he never thought he d consider in a million years. A love that goes off script: With their careers at risk, Nevaeh and Lamont have to convince the world that their scripted romance is more than just an act. But when fake seems to turn into something real, can Nevaeh trust her heart in a world where nothing is ever as it seems?"--
Keywords: Beauty operators -- Fiction; Actors -- Fiction; Man-woman relationships -- Fiction; African Americans -- Fiction; Celebrities in mass media; Fiction; Hollywood (Los Angeles, Calif.) -- Fiction; Large print books; Christian fiction; Romance fiction; Novels